2014
DOI: 10.1016/j.cell.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Identity Generated by Combinatorial Homophilic Interactions between α, β, and γ Protocadherins

Abstract: Summary Individual mammalian neurons express distinct repertoires of protocadherin (Pcdh) -α, -β and -γ proteins that function in neural circuit assembly. Here we show that all three types of Pcdhs can engage in specific homophilic interactions, that cell surface delivery of alternate Pcdhα isoforms requires cis interactions with other Pcdh isoforms, and that the extracellular cadherin domain EC6 plays a critical role in this process. Analysis of specific combinations of up to five Pcdh isoforms showed that Pc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
469
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(503 citation statements)
references
References 43 publications
30
469
4
Order By: Relevance
“…Each neuron expresses a subset of isoforms through a mechanism involving differential transcript initiation from promoters upstream of each variable exon (17,23,24). Our studies, confirmed by others, show that ␥-Pcdh proteins form cis multimers promiscuously but that these multimers interact strictly homophilically in trans (25,26). The differential expression of 22 isoforms thus allows, in theory, thousands of distinct adhesive interfaces to be specified by ␥-Pcdhs (27,28).…”
supporting
confidence: 60%
“…Each neuron expresses a subset of isoforms through a mechanism involving differential transcript initiation from promoters upstream of each variable exon (17,23,24). Our studies, confirmed by others, show that ␥-Pcdh proteins form cis multimers promiscuously but that these multimers interact strictly homophilically in trans (25,26). The differential expression of 22 isoforms thus allows, in theory, thousands of distinct adhesive interfaces to be specified by ␥-Pcdhs (27,28).…”
supporting
confidence: 60%
“…Intriguingly, the multimer formation occurs promiscuously among various isoforms, leading the authors of that study to predict that the 22 isoforms of Pcdhc could form 234,256 distinct adhesive interfaces. A recent study has further found that cells expressing different combinations of Pcdha, Pcdhb and Pcdhc aggregate through the homophilic transinteractions of the protocadherins that they express; however, these cells fail to co-aggregate with cells that express a different combination of protocadherins, even when the difference is only due to one isoform in the combination (Thu et al, 2014) (Fig. 2C).…”
Section: Single Cell Diversification Through Clustered Protocadherinsmentioning
confidence: 99%
“…Another member of the d1 subfamily, axial protocadherin (AXPC, Xenopus homolog of Pcdh1), is expressed along the axial mesoderm in Xenopus . (C) Cell-cell adhesion is induced only between cells expressing the same combination of clustered protocadherins (Thu et al, 2014). Expression of a Pcdha isoform alone does not induce cell-cell adhesion, probably due to its failure to transfer to the plasma membranes, whereas co-expression of Pcdha and Pcdhc isoforms induces cell-cell adhesion.…”
Section: Developmental Roles Of D1-protocadherinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific homophilic interactions and cell surface delivery of alternate isoforms depend upon cis interactions with other isoforms, extracellular domain. Mismatched isoforms are necessary for singlecell identity (Thu et al 2014). It is still unclear whether drug toxicity can influence the phenotypes of mRNA isoforms, or whether drug-induced changes in mRNA isoform patterns is a key molecular mechanism by which drugs can interrupt gene function by switching mRNA isoform production.…”
mentioning
confidence: 99%